(untitled) (KYAMC Journal, 2019)
Background: Surgical defects of oral cavity and orofacial region are challenging because of the aesthetic and functional demands and dynamic nature of the area. A multitude of reconstructive options are available and with the advent of musculocutaneous flaps and free microvascular tissue transfer, orofacial reconstruction has entered an era of sophistication whereby repair of defects of all types and sizes has become possible. Objectives: This study was conducted to evaluate the functional outcome, surface texture and complications of nasolabial flap for reconstruction in the buccal mucosal defects. Materials and Methods: A cross-sectional observational study was conducted 20 patients with clinical histological diagnosed squamous cell carcinoma (SCC;T1-T3 ) involving buccal mucosa attending in the Oral and Maxillofacial Surgery department of Dhaka Dental College and Hospital during this study period were included purposively in the study. All patients were treated by excision of the lesion and subsequent reconstruction of the defect by nasolabial flap. If indicated then patients received adjuvant radiotherapy. They were examined preoperatively, immediate postoperatively, on discharge and 3 months after operation. Data were analyzed by SPSS statistics (version 20) software. To find out the significance of the result one way ANOVA was conducted and the Post Hoc Test was done by LSD. Results: Among 20 patients 15% (3) patients developed infection, 15% (3) patients developed dehiscence. Trismus occurred in 5% (1) patient. In assessment of interincisal opening of the patients, 90% (18) presented with adequate interincisal opening but it has been reduced in 10% (2) patients after radiotherapy. In 90% (18) patients surface texture of the flap were smooth and in 10% (2) were partially smooth. Conclusion:The nasolabial flap has proved to be a useful and reliable option for reconstruction of defects of the buccal mucosa in order to allow wound closure without tension and maintain oral function. KYAMC Journal Vol. 10, No.-1, April 2019, Page 48-53